Application of HuTVeC Hydrological Model to Two Malaysian Watersheds - Choong, Wee Kang (2000)
HuTVeC, an acronym for Humid Tropical Vegetation and Climate hydrological model was developed by Amjad Nabi in 1997. This model includes the plant leaf dependent parameters such as the leaf area index, light extinction coefficient, canopy storage coefficient, etc., which are controlled by the vegetation type. The output of this model are the daily evapotranspiration, canopy storage and streamflow. The input data required for this model includes daily rainfall, minimum and maximum temperatures, minimum and maximum relative humidity and sunshine hours. Daily streamflow data is also required for model calibration and validation. Application of HuTVeC model was carried out in a 66 square kilometre Trolak watershed using continuous five-year data from 1982 to 1986. For model application to a bigger watershed, Tanjung Malim watershed with watershed area of 186 square kilometres was selected using continuous five-year data from 1988 to 1992. The results of the model application show that HuTVeC model underestimated the streamflow in both watersheds with up to 38.5% underestimation for Trolak watershed and up to 50.8% underestimation for Tanjung Malim watershed. From the analyses, these underestimated streamflow were due to overstated canopy interception by up to 5% and overstated transpiration of up to 9%. Better results were obtained when the maximum rainfall was used in place of average rainfall in the watershed. It is also found that if the ratio of modelled canopy interception to rainfall and the ratio of modelled transpiration to rainfall were maintained below 20% and 40% respectively, the modelled results were deemed acceptable. The study also found that HuTVeC model is able to produce annual streamflow for planning purposes with more than 60% probability that the modelled annual flow and observed annual are having the same mean with good correlation between monthly modelled flow and observed flow.